2020
DOI: 10.1074/jbc.ra120.015012
|View full text |Cite
|
Sign up to set email alerts
|

Wildtype σ1 receptor and the receptor agonist improve ALS-associated mutation-induced insolubility and toxicity

Abstract: Genetic mutations related to amyotrophic lateral sclerosis (ALS), a progressive neurological disease, have been discovered in the gene encoding sigma-1 receptor (σ1R). We previously reported that σ1RE102Q elicits toxicity in cells. The σ1R forms oligomeric states that are regulated by ligands. Nevertheless, little is known about the effect of ALS-related mutations on oligomer formation. Here, we transfected NSC-34 cells, a motor neuronal cell line, and HEK293T cells with σ1R-mCherry (mCh), σ1RE102Q-mCh or non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…amyotrophic lateral sclerosis is a progressive neurological disorder (28). in this disease, brain neuronal apoptosis was found to be inhibited after prolonged treatment with Sig-1r agonists (28). Altogether, these findings suggest that Sig-1R mediates protective effects against cell damage, whereby increasing Sig-1r activity can alleviate cell damage.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…amyotrophic lateral sclerosis is a progressive neurological disorder (28). in this disease, brain neuronal apoptosis was found to be inhibited after prolonged treatment with Sig-1r agonists (28). Altogether, these findings suggest that Sig-1R mediates protective effects against cell damage, whereby increasing Sig-1r activity can alleviate cell damage.…”
Section: Discussionmentioning
confidence: 95%
“…Sig-1r agonists have been previously shown to alleviate cerebral ischemia-reperfusion injury by reversing neuronal apoptosis and improving neurological function (27). amyotrophic lateral sclerosis is a progressive neurological disorder (28). in this disease, brain neuronal apoptosis was found to be inhibited after prolonged treatment with Sig-1r agonists (28).…”
Section: Discussionmentioning
confidence: 99%
“…ALS can be heritable or sporadic [ 80 ]. Genetic polymorphisms have been discovered in the gene that encodes the sigma-1 receptor, making a sigma-1 receptor agonist a plausible treatment target [ 81 ]. A homozygosity mapping study that sequenced the sigma-1 receptor gene revealed a mutation in the transmembrane domain that could be associated with juvenile ALS [ 82 ].…”
Section: Reviewmentioning
confidence: 99%